2019
DOI: 10.22159/ijap.2019.v11s5.t0050
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterizations of Self-Nanoemulsifying Drug Delivery System of Extract Petiveria Alliacea (Singawalang) Leaves

Abstract: Objective: Formulation of Singawalang leaves extract should be considered because the extract contains a variety of compounds so that there maybe a competitor in the absorption process and will cause the absorption of active ingredients in the gastrointestinal decline. One way to increase theabsorption and disposition of active ingredients on target organs is to use a nanoparticle formulation. Therefore, this study will conduct research onself-nanoemulsifying drug delivery system (SNEDDS) formulation of Singaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Propylene glycol as cosurfactant had a major influence on emulsification time. Mustika et al (2019) showed that the dispersion ability of propylene glycol±15 s was included in category A [18], capable to produce a nanoemulsion quickly in about 1 min [19] with a clear nanoemulsion display. This is in accordance with the results obtained in this study.…”
Section: Emulsification Time Testmentioning
confidence: 99%
“…Propylene glycol as cosurfactant had a major influence on emulsification time. Mustika et al (2019) showed that the dispersion ability of propylene glycol±15 s was included in category A [18], capable to produce a nanoemulsion quickly in about 1 min [19] with a clear nanoemulsion display. This is in accordance with the results obtained in this study.…”
Section: Emulsification Time Testmentioning
confidence: 99%
“…The SNEDDS formulation was formed from virgin coconut oil, Tween 80, and propylene glycol. The SNEDDS of P. alliacea leaf extract was made by adding P. alliacea leaf extract to the SNEDDS formulation [21].…”
Section: Plant Materialsmentioning
confidence: 99%
“…One of the disadvantages of P. alliacea leaf extract is that it contains complex active compounds, which may compete in the absorption process, resulting in a decline in the absorption of active compounds in the gastrointestinal tract [19,20]. Therefore, to overcome this problem, P. alliacea extract formulated in the form of a self-emulsifying drug delivery system (SNEDDS) is made [21]. The evaluation of the SNEDDS formulation of P. alliacea leaf extract on the diabetes treatment has not yet been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%